Development of a wear coefficient equation for the A A7075-B4C composite – steel interface - Venkatrami Reddy Veduru; Ranjith R; Kanulla Karthik; P Sasirekha (Materials Research Express)
In this research, an attempt was made to develop a wear equation for specific wear regimes that differs with temperature, sliding velocity, applied load, and sliding distance. The experimental runs were designed with the L25 Taguchi orthogonal array, and the uniform dispersion of reinforcement was confirmed using a scanning electron microscope. The presence of reinforcement hinders dislocation movement led to an augmentation in the composites’ hardness, while an elevation in temperature resulted in a decline in hardness due to the reduction of Pierls stresses. Owing to the formation of a Mechanical Mixed Layer (MML), the wear rate decreases with addition of volume fraction of B _4 C particles until 7.5%, beyond this MML break down and wear rate transit from mild to severe due to the direct metal contact. At 50 °C, the wear mode was abrasive and delamination; at 150 °C, it was abrasive plastic deformation; and at 250 °C, it was plastic flow of materials. Grooves, micro pits, micro cracks, ploughing and resolidified material were the distinct feature observed on the worn surface morphology. The modified wear equation was developed by incorporating reinforcement effect, specific wear regimes, temperature-dependent factors, and functional parameters.